Applying Value Analysis and Value Engineering to Develop a Popular Wheel Clamp - ALHODIANY, ZAKARYA MOHSEN MUTHANNA (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The work describes the basics of value analysis and value engineering and presents detailed overview of its distinct stages applicable to any merchandise with the aim of boosting its value. Besides, the paper examines the case of delivering a new popular wheel clamp on the market. The research discovers that one can accomplish it through improving the design of a specific model of the device in the framework of value analysis and value engineering. The enhancement consists in reduction of the number of components, implementation of the fool-proof technology, and taking advantage of the leverage. The activity gives rise to the improved design of an affordable wheel clamp.